Investigation of Varying Nitrogen Doses and Row Spacing Applications on the Chemical Composition of Evening Primrose (Oenothera lamarckiana L.) - SEKEROGLU, NAZIM (Asian Journal of Chemistry, 2010)
Evening primrose oil extracted from the seeds of evening primrose (Oenothera lamarckiana L.) is one of the most important sources of herbal medicine and food additives, recently. The effects of different nitrogen doses (0, 60, 120 and 180 kg ha-1) and row spacing applications (20, 40 and 60 cm) on the seed oil content and its fatty acid composition of evening primrose were studied in the Cukurova ecological conditions of Turkey during 2000 and 2001. In conclusion, varying nitrogen doses and row spacing applications had considerable effect the seed crude oil content and its chemical composition, the highest γ-linolenic acid content was obtained from 180 kg ha-1 nitrogen dose and 40 cm row spacing application.